Incidência de lesões musculoesqueléticas e fatores de risco em praticantes de CrossFit®: um estudo prospectivo - Szeles, Paulo Roberto de Queiroz [UNIFESP] (2018)
Objective: The objective of this study was to investigate the CrossFit®related musculoskeletal injury incidence and the associated risk factors. Methods: A prospective 12week followup of 452 individuals selected from CrossFit® boxes from the metropolitan area of São Paulo, Brazil, in 2016 and 2017. Data were collected from an initial sample characterization questionnaire followed by six electronic questionnaires sent biweekly by email with questions regarding training frequency and injury occurrence. A timeloss injury definition was used and injuries were classified by the anatomical location and injury type. Risk factors such as age, body mass, previous injuries, experience (years of practice), training load, preventive exercises, use of protective equipment, supervision of trainers, and participation in competitions were investigated. Data analysis were performed through descriptive statistics and logistic mixed models. Results: 1618 responses out of 406 participants (89.8%) resulted in a cumulative incidence rate of 38.9% (n = 158) and incidence density, based on anatomical location, of 29.1 per 1000 hours of exposure (n = 379) and 23.7 per 1000 hours of exposure, based on type of lesion (n = 309). The shoulders (20.1%), lumbar spine (17.9%), and knees (9.5%) were the most affected locations and muscle injuries (45.0%), joint pain (24.6%), and tendinopathies (12.9%) were the most frequent types. The average exposure to CrossFit® was 3.9 times per week and the majority of participants trained with Scaled load 51.5%, followed by the group that alternated loads 27.1% (Rx or Scaled) and trained with Rx load 21.3%. The mean severity according to the numeric scale of pain was 5 (4.7 to 5.3) and time loss was 2.7 (2.3 to 3.1) days. Injury associated factors were: varying training load 4.67 (2.47 to 8.83, CI 95%) and previous injury (2.35 to 5.66, CI 95%). CrossFit® experience (> 1 year) 0.70 (0.52 to 0.95, CI 95%) was a protection factor. Other investigated variables were not associated with CrossFit® injuries. Conclusion: incidence density in the present study was about ten times higher than the currently reported, 29.1 per 1000 hours of exposure (anatomical location) and 23.7 per 1000 hours of exposure (type of lesion). The variables previous lesions and variation of the training load (Rx or Scaled) were risk factors associated with injury and experience (years of practice), a protection factor.